Improvement of Patients’ Knowledge, Attitude, and Practice on Tuberculosis Treatment Using Video and Leaflet - Dameria, Dameria; Hulu, Victor Trismanjaya; Siregar, Santy Deasy; Manalu, Putranto; Samosir, Frans Judea; Rambe, Fadilah Ummul Choiriyah; Hasibuan, Nadilla (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2023)
Background: The effectiveness of Tuberculosis (TB) treatment outcomes for patients is currently suboptimal, posing a significant challenge to comprehensive efforts aimed at eradicating the disease. To address this problem, several studies have proposed that the implementation of health education initiatives have the potential to enhance treatment adherence and behavior of patients. Therefore, this study aims to assess the efficacy of health education programs using video and leaflet modalities.Method: This was a quasi-experimental study with a non-randomized pretest-posttest control group design. The sample population consisted of 85 TB patients at the Kenanga Health Center, Tegal Sari Mandala II, Medan Denai District, Medan City in 2022. Furthermore, the samples size was obtained using a purposive sampling method, involving 64 patients, which were evenly divided into two groups, namely intervention and control. The controls and intervention groups were educated using leaflet and video media, respectively. Pre-test and post-test were given to all the participants using the same instrument. A post-test was administered on the twenty-fifth day, where the materials were the same as those used at the pre-test stage. The data collected in this study were analyzed using the Wilcoxon, Mann-Whitney, and N-Gain tests.Results: There were significant differences between knowledges, attitudes, and practices of the participants before and after being given the interventions. Furthermore, knowledges, attitudes, and practices scores increased after the interventions were administered. Based on the results, health education using video (N-Gain score of 76.82) improved behavior of TB patients compared to the use of leaflet (N-Gain score of 49.74). After being educated, people with TB were expected to exhibit higher treatment adherence and adoption of healthy lifestyles.